Effect of Scanner Type on Marginal Adaptation of e.max CAD Crowns - Hamid Jalali; Habib Hajmiragha; Farzaneh Farid; Siavash Tabatabaie; Samar Jalali (Islamic Dental Association of Iran, 2018)
Background and Aim: Marginal adaptation has a significant role in the success and longevity of indirect restorations. This experimental study compared the effect of intraoral and extraoral scanning on the marginal adaptation of the crowns which was made using the CEREC AC system. Materials and Methods: A Typodont maxillary first molar was prepared and served as the master die for an all-ceramic restoration. In the first group, the model was scanned ten times directly by the intraoral scanner. In the second group, ten conventional impressions were made from Typodont, and the extraoral scanner scanned the resulting gypsum casts. The data was used to design and build crowns from IPS e.max CAD blocks. The crowns were placed on the prepared tooth, and the marginal gap was measured at 16 points by a stereomicroscope at ×35 magnification. Collected data were analyzed using t-test. Results: The mean marginal gap for intraoral and extraoral groups were 74.83 ± 10.07 μm and 102.56 ± 6.89 μm respectively. The gap was significantly less in the intraoral group (P-value = 0.001). Conclusion: Marginal adaptation was clinically acceptable in both groups, although the results of intraoral scanning showed significantly lower gap than extraoral scanning.